2009
DOI: 10.1111/igc.0b013e3181aae1fb
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment With Progestin and Pregnancy Outcomes in Endometrial Cancer

Abstract: Conservative treatment with progestin can be considered a good therapeutic option in patients with well-differentiated early-stage endometrioid endometrial adenocarcinoma who wish to preserve their uteri or become pregnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 19 publications
0
57
0
Order By: Relevance
“…Studies at various institutions have reported the results of fertility-sparing treatment for EC using progesterone preparations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, as the number of cases have been low, the efficacy of such treatment has yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Studies at various institutions have reported the results of fertility-sparing treatment for EC using progesterone preparations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, as the number of cases have been low, the efficacy of such treatment has yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Today exist the possibility to detect early stage well-differentiated tumors that can be treated with resection of the lesion and progestin therapy. (29) Epithelial ovarian cancer continues to be treated radically with loss of reproductive organs. But increasing understanding of germ cell malignancies, borderline tumours of the ovary and epithelial tumors at stage IA grade I, has led to a more conservative approach to these neoplasms and often a single oophorectomy will be performed where in the past, a hysterectomy and/or bilateral oophorectomy would have been the treatment of choice.…”
Section: Surgical Managementmentioning
confidence: 99%
“…A review of 99 women treated within nine different studies reported an overall complete response rate of 54% with a total of 37 live births [8]. More recently, response rates of 55-63% have been reported with the use of high-dose progestogens [9,10]. Even higher responses of up to 82% are reported for atypical hyperplasia [9].…”
Section: Fertility-sparing Treatmentmentioning
confidence: 99%